If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 12)(x + -15) = 0 Reorder the terms: (12 + x)(x + -15) = 0 Reorder the terms: (12 + x)(-15 + x) = 0 Multiply (12 + x) * (-15 + x) (12(-15 + x) + x(-15 + x)) = 0 ((-15 * 12 + x * 12) + x(-15 + x)) = 0 ((-180 + 12x) + x(-15 + x)) = 0 (-180 + 12x + (-15 * x + x * x)) = 0 (-180 + 12x + (-15x + x2)) = 0 Combine like terms: 12x + -15x = -3x (-180 + -3x + x2) = 0 Solving -180 + -3x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (-12 + -1x)(15 + -1x) = 0Subproblem 1
Set the factor '(-12 + -1x)' equal to zero and attempt to solve: Simplifying -12 + -1x = 0 Solving -12 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -1x = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -1x = 0 + 12 -1x = 0 + 12 Combine like terms: 0 + 12 = 12 -1x = 12 Divide each side by '-1'. x = -12 Simplifying x = -12Subproblem 2
Set the factor '(15 + -1x)' equal to zero and attempt to solve: Simplifying 15 + -1x = 0 Solving 15 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -1x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -1x = 0 + -15 -1x = 0 + -15 Combine like terms: 0 + -15 = -15 -1x = -15 Divide each side by '-1'. x = 15 Simplifying x = 15Solution
x = {-12, 15}
| (5x+3)/4=-12 | | 7-9(5t-4)=47 | | 7/4x+4/3=-8 | | x=0.1666666667 | | 15c+12=2 | | 110-x=11 | | 2(1+3x)=26 | | 3t-(t+5)=6+(t+1) | | 3(4p+5)-11p= | | 8-7n-21=85 | | 711.67*2.5%= | | 2/3=4x/6 | | 15y/5=x | | x^4+6x^3+14x^2+15x-6=0 | | (4x+3)/12x=36 | | -226.8=21.6 | | (-50)-(9)= | | -2226.8=21.6y | | (7)-(-3)= | | 45x^2-60x+20=0 | | 49/n=7 | | ax+2a=4x+7a | | 4/(x-1)=(x+1)/12 | | -5+7t+16+t=11t-3-t | | y/9=5+0 | | 15x^2-x-10=18 | | 3y+2x=-4 | | 4y-13-5y=-12y+9+8y | | 3x+3(5d-18)=108 | | M=3n+8 | | -113=-(8+8x)-7x | | 11y-1+5y=65y-36 |